Pengaruh Citra Merek Terhadap Loyalitas Pelanggan pada Perusahaan Penerbitan: Survei pada Pengikut Akun Instagram Penerbit Mediakita - Nadhirah Fahrani; Mohammad Benny Alexandri; Ratih Purbasari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the impact of brand image on customer loyalty at Mediakita Publisher, a publishing company. Brand image and customer loyalty are the objects of this research as independent and dependent variables. This research employs a descriptive quantitative methodology utilizing a survey research design. The study's population comprised all followers of the Mediakita Publisher Instagram account, with a sample size of 100 respondents. For this analysis, SPSS version 25 is being used, and the results indicated a positive and significant impact of brand image on customer loyalty at Mediakita Publisher, with an influence of 36.9%. Increasing contact with account followers through interactive material, publishing books on customer-interested subjects, and releasing special edition books are some ideas that can be made.